Преобразуйте в многочлен : 1)(a-3)^2 (2y+5)^2 (4a-b)(4a+b) (X^2+1)(x^2-1)

0 голосов
24 просмотров

Преобразуйте в многочлен :
1)(a-3)^2
(2y+5)^2
(4a-b)(4a+b)
(X^2+1)(x^2-1)


Математика (25 баллов) | 24 просмотров
Дан 1 ответ
0 голосов

(  а - 3 )² =  a² - 6a + 9 
( 2y + 5 )² = 4y² + 20y + 25 
( 4a - b )*( 4a + b ) = 16a² - b²
( x² + 1 )*( x² - 1 ) = x⁴ - 1 

0

Пожалуйста

0

Выполните действия: 1.2(3x-2y) (3x+2y) 2.(a^3+b^2)^2 3.(a-5)^2 - (a+5)^2 Преобразуйте в многочлен: (а-2)(а+2) - 2а(5-а) (y-9)^2-3y(y+1) 3(x-4)^2-3x^2